2012
DOI: 10.1002/pmic.201200060
|View full text |Cite
|
Sign up to set email alerts
|

Proteomes of umbilical vein and microvascular endothelial cells reflect distinct biological properties and influence immune recognition

Abstract: Human umbilical vein endothelial cells (HUVEC) are widely used as a source of endothelial cells (EC). However, HUVEC characteristics cannot be extrapolated to other types of EC, particularly microvascular ECs. Our objective was to compare the proteomes of microvascular ECs and HUVEC. Proteomes of HUVEC and human microvascular pulmonary EC (HMVEC-P) and dermal EC (HMVEC-D) from healthy Caucasian donors were compared by 2D DIGE and MS. Fatty acid binding proteins 4 and 5 were among the 159 and 30 proteins spots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…specifically studied the mechanical properties of VSMC and demonstrated that elastin expression and extracellular matrix deposition vary along arterial tree and that it could be correlated to stiffness and shear stress reactivity of these cells . We recently demonstrated that, according to their origin, endothelial cells have very distinct protein content and that it could reflect different biological properties and influence immune recognition . The unique protein content observed in PAH‐SMC might be the cause or the consequence of the pathological process and it might modify cell recognition by auto‐antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…specifically studied the mechanical properties of VSMC and demonstrated that elastin expression and extracellular matrix deposition vary along arterial tree and that it could be correlated to stiffness and shear stress reactivity of these cells . We recently demonstrated that, according to their origin, endothelial cells have very distinct protein content and that it could reflect different biological properties and influence immune recognition . The unique protein content observed in PAH‐SMC might be the cause or the consequence of the pathological process and it might modify cell recognition by auto‐antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…[25], [26] HMVEC have been reported to differ from HUVEC in the expression of chemokine receptors and other surface markers. [27], [28] Recent study showed different proteome profiles between HUVEC and HMVEC, which could result in distinct biological properties and explain their different responses to KMSC-MPs [29].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged exposure times for HMVECs compared to HUVECs were secondary to published differences in immune phenotype of HMVECs compared to HUVECs, as well as internal testing demonstrating prolonged development of a LPS tolerant phenotype in HMVECs at 16 hours after the second agonist exposure compared to a similar LPS tolerance phenotype seen in HUVECs after 6 hours of the second agonist (see Fig S1). 22 …”
Section: Methodsmentioning
confidence: 99%